Recent advances in vascular disrupting agents in cancer therapy. (September 2014) - Porcù, Elena; Bortolozzi, Roberta; Basso, Giuseppe; Viola, Giampietro
Vascular disrupting agents (VDAs) are an important class of compounds that exhibit selective activity against pre-existing tumor vasculature, causing rapid shutdown of the tumor blood flow and consequent necrosis of the tumor mass. The VDAs can be divided into flavonoid compounds, which are related to flavone acetic acid, and tubulin-binding agents. Tubulin-binding agents represent the largest group of VDAs and are characterized by different chemical structures, although most of them are derivatives of the lead compound combretastatin (CA-4). They demonstrated clinical activity, although recent findings have established that they have insufficient activity as single agents. Several resistance mechanisms occur, such as the resistance of the tumor rim cells, while promising results have been described in combination with other chemotherapeutics.